Forced convection heat transfer in a power-law fluid flow in a circular duct - Kamişli, Fethi (Turk Isı Bilimi ve Teknigi Dernegi, 2019)
The dimensionless temperature, the entropy generation rate and Nusselt number for a power-law fluid flow in a pipe with constant wall heat flux have been determined as functions of the Brinkman number, power-law index, dimensionless temperature difference and group parameters. The one-dimensional approximate equations with viscous dissipation for the energy, the entropy and the Nusselt number for a power-law fluid flow have been determined by accounting for the order of magnitude of terms and asymptotic techniques. The one-dimensional approximate equations of the velocity, the temperature and the entropy generation rate have been analytically solved to determine the velocity, the temperature and the entropy distributions in a non-Newtonian fluid flow as functions of the effective process parameters. The derived equation with viscous dissipation term for Nusselt number depending on power-law index and Brinkman number covers all types of pseudo-plastic and dilatant fluid behaviors. It has found that the Brinkman number is quite effective on the temperature, the Nusselt number and the entropy generation number. The Nusselt number has exponentially decreased with increasing Brinkman number at values of power-law index. ©2019 TIBTD Printed in Turkey.
Keywords: Brinkman number; Entropy generation; Power-law fluid flow; Viscous dissipation